The theory of Social Self-Management in Nildo Viana: The theory of Social Self-Management in Nildo Viana (Élisée - Revista de Geografia da UEG, 2020)
Discute-se neste texto a concepção de Autogestão Social tal como elaborada por Nildo Viana. Para tanto, realizou-se uma análise nos livros e artigos do autor que tocam diretamente nesta matéria. O estudo do material teve como objetivos: a) identificar o processo de engendramento da Autogestão Social por meio da autogestão das lutas proletárias; b) identificar como sua teoria da Autogestão está imbricada em sua teoria do capitalismo; c) analisar os processos que obstam o estabelecimento da Autogestão; d) criticar as apropriações ideológicas do termo Autogestão; e) apontar os elementos gerais estruturadores da sociedade autogerida.Resumen: Este texto discute el concepto de autogestión social desarrollado por Nildo Viana. Con este fin, se llevó a cabo un análisis de los libros y artículos del autor que abordan directamente este asunto. El estudio del material tenía como objetivos: a) identificar el proceso de engendrar la autogestión social a través de la autogestión de las luchas proletarias; b) identificar cómo su teoría de la autogestión está entrelazada con su teoría del capitalismo; c) analizar los procesos que dificultan el establecimiento de la autogestión; d) criticar las apropiaciones ideológicas del término autogestión; e) señalar los elementos generales estructuradores de la sociedad autogestionada.Palabras-clave: Autogestión Social. Marxismo. Autogestionario. Nildo Viana.The theory of Social Self-Management in Nildo VianaAbstract: This text discusses the concept of Social Self-Management as developed by Nildo Viana. An analysis was carried out on the author's books and articles that directly address this matter. The study of the material had as objectives: a) to identify the process of engendering Social Self-Management through the self-management of proletarian struggles; b) identify how his theory of self-management is intertwined with his theory of capitalism; c) analyze the processes that hinder the establishment of Self-Management; d) criticize the ideological appropriations of the term Self-management; e) point out the general structuring elements of the self-managed society.Keywords: Social Self-Management. Self-managing. Marxism. Nildo Viana.
Keywords: Social Self-Management. Self-managing. Marxism. Nildo Viana.